The roles of ubiquitin modifying enzymes in neoplastic disease - Kumari, N.; Jaynes, P.; Saei, A.; Iyengar, P.; Richard, J.; Eichhorn, Pieter (Elsevier BV, 2017)
© 2017 Elsevier B.V. The initial experiments performed by Rose, Hershko, and Ciechanover describing the identification of a specific degradation signal in short-lived proteins paved the way to the discovery of the ubiquitin mediated regulation of numerous physiological functions required for cellular homeostasis. Since their discovery of ubiquitin and ubiquitin function over 30 years ago it has become wholly apparent that ubiquitin and their respective ubiquitin modifying enzymes are key players in tumorigenesis. The human genome encodes approximately 600 putative E3 ligases and 80 deubiquitinating enzymes and in the majority of cases these enzymes exhibit specificity in sustaining either pro-tumorigenic or tumour repressive responses. In this review, we highlight the known oncogenic and tumour suppressive effects of ubiquitin modifying enzymes in cancer relevant pathways with specific focus on PI3K, MAPK, TGFß, WNT, and YAP pathways. Moreover, we discuss the capacity of targeting DUBs as a novel anticancer therapeutic strategy.